Process Resilience Analysis Framework (PRAF): A systems approach for improved risk and safety management. (May 2018) - Jain, Prerna; Pasman, Hans J.; Waldram, Simon; Pistikopoulos, E.N.; Mannan, M. Sam
Abstract: Risk management challenges and continuous increase of global public aversion to hazards and risks associated with the process industry have been observed in the recent years. In order to manage process industry risk, several studies and methods have been developed and are currently used. The authors believe that two types of interacting factors: 1) technical (equipment malfunction, process parameter variation), and 2) social (regulations/policy, human and organizational factors) are important in assessment of risk for a process system. However, current methods are based on analysis of either technical factors, often quantitatively, or social factors, usually qualitatively. Apart from failure to establish all critical scenarios due to either factors, their combined and interactive effects are seldom considered. This research need calls for the development of a holistic and integrated systems framework for effective risk management, although full coverage of possible mishaps will be utopian. The application of the resilience engineering perspective is gradually being explored as an approach for considering the dynamics of socio-technical aspects based on systems theory to provide a safety net. This paper presents a novel framework - Process Resilience Analysis Framework (PRAF) for incorporating both technical and social factors in an integrated approach. This is based on four aspects: Early Detection (ED), Error Tolerant Design (ETD), Plasticity (P) and Recoverability (R). The resilience methodology emphasizes dynamics, unforeseen and even unknown types of threats, uncertainty, systems degradation and complex interactions. With resilience metrics a combined framework for predictability, survivability and recoverability, all via dynamic analysis, is introduced. PRAF primarily focuses on early detection of unsafe domains of operation, assessment of aggregate risks and prioritization of safety barriers during process upset situations and reduction in response time resulting in a reduced frequency of loss of containment events (LoC), reduced consequences and enhanced recovery. The paper describes the concepts and principles of the PRAF as a first step. Highlights: Combination of technical and social factors for risk assessment. Holistic and integrated systems framework for effective risk management. Application of the resilience engineering perspective. Dynamics of socio-technical aspects based on systems theory. Resilience metrics as a combined framework for predictability, survivability and recoverability.